2016
DOI: 10.1371/journal.pntd.0004527
|View full text |Cite
|
Sign up to set email alerts
|

Geological Changes of the Americas and their Influence on the Diversification of the Neotropical Kissing Bugs (Hemiptera: Reduviidae: Triatominae)

Abstract: BackgroundThe family Reduviidae (Hemiptera: Heteroptera), or assassin bugs, is among the most diverse families of the true bugs, with more than 6,000 species. The subfamily Triatominae (kissing bugs) is noteworthy not simply because it is the only subfamily of the Reduviidae whose members feed on vertebrate blood but particularly because all 147 known members of the subfamily are potential Chagas disease vectors. Due to the epidemiological relevance of these species and the lack of an efficient treatment and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
177
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(202 citation statements)
references
References 58 publications
17
177
2
6
Order By: Relevance
“…Moreover, we argue that this was a unique event in the karyotype evolution of the Triatoma from South America, because, in addition to T. melanocephala and T. vitticeps , the only species that also presents fragmentation of the X chromosome is T. tibiamaculata 2n = 23 (20A + X 1 X 2 Y) [38]. However, the analysis provided by Justi et al [19] allows us emphasise that this species inherited this number of chromosomes from the common ancestor shared with the Panstrongylus (a genus in which most of the species also have 23 chromosomes).
Fig. 2Karyotype evolution of the South American subcomplexes.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we argue that this was a unique event in the karyotype evolution of the Triatoma from South America, because, in addition to T. melanocephala and T. vitticeps , the only species that also presents fragmentation of the X chromosome is T. tibiamaculata 2n = 23 (20A + X 1 X 2 Y) [38]. However, the analysis provided by Justi et al [19] allows us emphasise that this species inherited this number of chromosomes from the common ancestor shared with the Panstrongylus (a genus in which most of the species also have 23 chromosomes).
Fig. 2Karyotype evolution of the South American subcomplexes.
…”
Section: Resultsmentioning
confidence: 99%
“…However, these species exhibit several similar characteristics, including morphological [27], cytogenetic [14], and phylogenetic [19] features, similarities which support the creation of a new subcomplex. Thus, this study aimed to describe, for the first time, the T. vitticeps subcomplex, highlighting the main phenotypic and genotypic characteristics that support the grouping of these species and how this subcomplex is distinct from the others present in South America.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our finding of the divergent taxon in a single cave system in Belize supports this hypothesis (although more extensive sampling is necessary to confirm this), and other cave populations are monophyletic with T. dimidiata s.s. Work has just begun on understanding the environmental and geological forces that have separated the Triatominae (Justi et al, 2016) and specifically T. dimidiata taxa (Gómez-Palacio et al, 2015). Clarity of how many taxa are under the T. dimidiata umbrella will facilitate these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Justi et al (2014Justi et al ( , 2016 claim that although the complexes and subcomplexes show no taxonomic validity they must be monophyletic groups. Thus, the authors presented a phylogenetic reconstruction for the species groupings proposed by Schofield and Galvão (2009) and observed that many groups are not monophyletic (brasiliensis, maculata, matogrossensis, flavida and sordida subcomplexes).…”
Section: Scientific Notementioning
confidence: 99%
“…Recently, by means of dated phylogeny was supported that the ancestral of Nesotriatoma arrived in the Antillean islands approximately 14.8-18.8 millions of years (associated with rodent subfamily Capromyinae) (Justi et al, 2016) and by phylogenetic analysis we can see that Nesotriatoma and Panstrongylus share an ancestor comum (Justi et al, 2014(Justi et al, , 2016. Was suggested that the ancestor of these vectors presented karyotype 2n = 23 and that during the divergence and karyotype evolution of species occurred one event punctual of simploidy in the autosome of P. megistus and agmatoploidy in the X sex chromosome of P. lutzi (Alevi and Azeredo-Oliveira, 2018).…”
Section: Scientific Notementioning
confidence: 99%